2016
DOI: 10.1093/jrr/rrw093
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of whole-body gamma radiation–induced damages by Clerodendron infortunatum in mammalian organisms

Abstract: Several phytoceuticals and extracts of medicinal plants are reported to mitigate deleterious effects of ionizing radiation. The potential of hydro-alcoholic extract of Clerodendron infortunatum (CIE) for providing protection to mice exposed to gamma radiation was investigated. Oral administration of CIE bestowed a survival advantage to mice exposed to lethal doses of gamma radiation. Radiation-induced depletion of the total blood count and bone marrow cellularity were prevented by treatment with CIE. Damage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Clerodendrum infortunatum rich in flavonoids and saponins is used in Ayurvedic and Siddha traditional medicine. Its hydro-alcoholic extract reduces radiation-induced damage to intestinal crypt cells and suppress BCL2-associated X protein (Bax)/B-cell lymphoma (Bcl-2) ratio, DNA repair gene ataxia telangiectasia mutated (ATM) and COX-2 gene in mice exposed to whole-body γ-radiation (Chacko et al, 2017 ).…”
Section: Mitigation Of Gastrointestinal Toxicity By Regulating Gastromentioning
confidence: 99%
“…Clerodendrum infortunatum rich in flavonoids and saponins is used in Ayurvedic and Siddha traditional medicine. Its hydro-alcoholic extract reduces radiation-induced damage to intestinal crypt cells and suppress BCL2-associated X protein (Bax)/B-cell lymphoma (Bcl-2) ratio, DNA repair gene ataxia telangiectasia mutated (ATM) and COX-2 gene in mice exposed to whole-body γ-radiation (Chacko et al, 2017 ).…”
Section: Mitigation Of Gastrointestinal Toxicity By Regulating Gastromentioning
confidence: 99%
“…Interestingly, DNA damage has been A c c e p t e d M a n u s c r i p t 20 detected not only in target organs but also in non-target organs [338]. The comet assay in rodents is also used to detect DNA damage induced by physical agents, such as ionizing γradiation [339][340][341][342], radiofrequency radiation [343][344][345], microwave radiation [346,347] and/or UV radiation [348][349][350] as well as loud noise as one of the major environmental threats to public health [351][352][353]. These studies are often performed in order to evaluate the protective potential of various natural products, e.g.…”
Section: Laboratory Mammalsmentioning
confidence: 99%
“…Additionally, the overexpression of COX-2 in NCI-H460 cells reduced the radiation sensitivity induced by gefitinib; however, no direct association was determined between the activation of ATM and expression of COX-2 ( 29 ). Chacko et al ( 30 ) determined that the hydro-alcoholic extract of Clerodendron infortunatum (CIE) reduces the total body gamma-ray radiation exposure in mice. Additionally, in the intestinal tissue of irradiated animals, following CIE treatment, the expression levels of ATM, but not its phosphorylated form, were elevated; however, the expression of COX-2 was reduced ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chacko et al ( 30 ) determined that the hydro-alcoholic extract of Clerodendron infortunatum (CIE) reduces the total body gamma-ray radiation exposure in mice. Additionally, in the intestinal tissue of irradiated animals, following CIE treatment, the expression levels of ATM, but not its phosphorylated form, were elevated; however, the expression of COX-2 was reduced ( 30 ). In a previous study by Kim and Pyo ( 31 ), it was reported that treatment with the mixture of 17-AAG, an inhibitor of heat shock protein 90, and celecoxib, an inhibitor of COX-2, increased the sensitivity of various human cancer cells to radiation through downregulating ATM and ATR ( 31 ).…”
Section: Discussionmentioning
confidence: 99%